An analytical approach to study educational inequalities: 10 hypothesis tests in PIRLS 2006 - Caro, D; Lenkeit, J (2012)
The paper draws on the work of Willms [2006. Learning divides: Ten policy questions about the performance and equity of schools and schooling systems. Montreal: UNESCO Institute for Statistics] to present an analytical approach to the study of academic achievement disparities related to family socioeconomic status. The approach is illustrated by evaluating 10 hypotheses with two-level and three-level hierarchical linear models using data from the Progress in International Reading Literacy Study 2006. For each hypothesis, the underlying theory, statistical model, and critical model test are presented and the results are discussed. The analytical approach can be generalized to other studies and data sets. The results help to understand how inequalities are configured at the within-country and between-country levels. © 2012 Copyright Taylor and Francis Group, LLC.